Ketimpangan Akses Pendidikan Islam: Studi Kasus di Tambing Kekeq Aik Berik - Ulan Susilawati; Fathurrahman Muhtar; Ismail (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to analyze the inequality in access to Islamic education in Tambing Kekeq Hamlet, Aik Berik Village, Central Lombok Regency, by examining the factors that influence this disparity and its implications for the sustainability of community education. Educational inequality in this context is understood as a structural phenomenon influenced by geographic conditions, economic conditions, educational infrastructure, and policies that are not fully responsive to remote areas. This study uses a qualitative approach with a case study design. Data were collected through participatory observation and in-depth interviews with five respondents consisting of parents, students, community leaders, teachers, and village officials. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing and verification. The results show that the inequality in access to Islamic education in the study area is caused by geographic isolation that hinders student mobility, limited teaching staff and educational facilities, and economic pressures of an agrarian community that often makes education a low priority. These conditions result in low educational participation, high absenteeism rates, and the emergence of a gap in religious literacy between central and peripheral areas. These findings confirm that educational inequality is multidimensional and interconnected, forming a cycle of educational injustice. The implications of this research point to the need for more affirmative and region-based education policies, including strengthening educational infrastructure, equitable distribution of teaching staff, and innovative educational services based on geographic accessibility. This approach is crucial for realizing a more inclusive and equitable distribution of Islamic education in remote areas.